2022
DOI: 10.51558/1840-4561.2022.19.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fundamental Motor Skills in Boys and Girls

Abstract: The aim of the study was to assess gross motor skills between boys and girls of preschool and primary school age. The study included a total sample of 83 respondents (49.3% boys) with an average chronological age of 6.14 ± 2.25 years. The Test of Gross Motor Development–3rd Edition (TGMD-3) was used to verify the set research goal. Research data were analyzed by the method of parametrical statistics. To determine the differences in gross motor skills between boys and girls, t-test was used for an independent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…What determines characteristics of child's movements, such as nimble, fast and precise, are motor abilities (Starc et al, 2004). The research has shown that third period of motor development is the most delicate and it includes fundamental motor abilities that encompass preschool period and early school age of a child (Sabo 2002; Cvetković, Popović and Jakšić, 2007 cited in Mehmedinović et al, 2022). Fundamental motor skills are basic goal-directed movement patterns that are an integral part of advanced movement skills (Clark & Metcalfe 2022).…”
Section: Introductionmentioning
confidence: 99%
“…What determines characteristics of child's movements, such as nimble, fast and precise, are motor abilities (Starc et al, 2004). The research has shown that third period of motor development is the most delicate and it includes fundamental motor abilities that encompass preschool period and early school age of a child (Sabo 2002; Cvetković, Popović and Jakšić, 2007 cited in Mehmedinović et al, 2022). Fundamental motor skills are basic goal-directed movement patterns that are an integral part of advanced movement skills (Clark & Metcalfe 2022).…”
Section: Introductionmentioning
confidence: 99%